The Effect of Hot Air Flow Velocity on The Drying Characteristics of Turmeric in A Rotary Dryer - Lalu Sultan Giri Tanjung; Rudy Sutanto; Mirmanto (Mechanical Engineering Department - Semarang State Polytechnic, 2025)
Turmeric (Curcuma longa) is a rhizome plant widely used in the food, pharmaceutical, and cosmetic industries. This study aims to determine the characteristics of turmeric after the drying process and to analyze the effect of variations in hot air flow rate on moisture content reduction, drying rate, and thermal efficiency. Although various studies on turmeric drying have been conducted, most of these studies only tested one parameter, such as cylinder speed, drying temperature, and airflow rate, without considering the interaction of hot airflow rate in the rotary dryer system. The drying method in this study used a rotary dryer with a heat source from LPG combustion, at hot air flow rates of 5.2 m/s, 7.9 m/s, and 9.1 m/s with a drum rotation speed of 6 rpm for 360 minutes. The results showed that higher hot air flow rates accelerated the drying process. Optimal conditions were achieved at a speed of 9.1 m/s with a moisture content of 43.97%. Although drying was faster at higher speeds, the best thermal efficiency (23.36%) occurred at a speed of 7.9 m/s. Meanwhile, at a speed of 9.1 m/s, efficiency decreased to 22.39%.